2021
DOI: 10.3390/cancers13061309
|View full text |Cite
|
Sign up to set email alerts
|

HERC1 Regulates Breast Cancer Cells Migration and Invasion

Abstract: Tumor cell migration and invasion into adjacent tissues is one of the hallmarks of cancer and the first step towards secondary tumors formation, which represents the leading cause of cancer-related deaths. This process is considered an unmet clinical need in the treatment of this disease, particularly in breast cancers characterized by high aggressiveness and metastatic potential. To identify and characterize genes with novel functions as regulators of tumor cell migration and invasion, we performed a genetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…It may relate to the inter-heterogeneity in different studies and samples. Similar to this research, Rossi et al have also revealed that HERC1 can regulate cell migration and invasion, and has an inverse correlation with breast cancer patients OS [ 47 ]. In short, the mRNAs in circRNA‐related ceRNA networks may have key roles in the progression of NSCLC patients.…”
Section: Discussionsupporting
confidence: 74%
“…It may relate to the inter-heterogeneity in different studies and samples. Similar to this research, Rossi et al have also revealed that HERC1 can regulate cell migration and invasion, and has an inverse correlation with breast cancer patients OS [ 47 ]. In short, the mRNAs in circRNA‐related ceRNA networks may have key roles in the progression of NSCLC patients.…”
Section: Discussionsupporting
confidence: 74%
“…HERC E3s are previously reported to have pivotal roles in many cancers. For instance, HERC1 was indicated to modulate the migration and invasion in breast cancer cells [19]. HERC2 was Fig.…”
Section: Discussionmentioning
confidence: 99%
“…reported to have an important function in the p53-MDM2 axis and might provide novel insight in cancers [20]. HERC4 interacts with miRNA and induces breast cancer progression via inhibiting LATS1 [19]. HERC5 is identified to be a potential prognostic biomarker for breast cancer via bioinformatics analysis [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations